Współczesny spór o istotę i zakres wychowania personalistycznego w Polsce - Śliwerski, Bogusław (Annales. Etyka w Życiu Gospodarczym, 2011)
The object of analysis is the personality education, train of thought pedagogic the most exposed of the conflict as the result of political disputes. The main problem of absence the research and specialist literature about personality education in the period of the socialism, was caused the political and ideological reasons. In the state democratic, this same, became an object of the marginality and social exclusion in public and pedagogic debate. Important is the question – why, from what reason, we are questioning personality in pedagogic and we are giving rise for formulating alternatives towards him. This situation is supporting to creating another – non personal direction in pedagogic, against contents and the structure of the social functioning.